Psychometric evaluation of a modified health belief model scale for breast self-examination - Resti Wahyuni; Diana Setiyawati (Jurnal Ilmiah Psikologi Terapan, 2026)
Low participation in early breast cancer detection remains a public health concern in Indonesia. This study contextually modified a Health Belief Model (HBM)-based instrument assessing Indonesian women’s beliefs about breast cancer and breast self-examination (BSE). Behavioral indicators were derived from open-ended responses, followed by psychometric evaluation among women aged 20 years and older. Evaluation included content validity, confirmatory factor analysis, nomological associations with health literacy, and reliability assessment using McDonald’s omega. Item refinement yielded a 21-item instrument measuring perceived susceptibility, perceived benefits, and perceived barriers. The three-factor model demonstrated acceptable fit (CFI = .990, TLI = .989, RMSEA = .063), with factor loadings supporting the adequacy of the retained items. Health literacy was positively associated with perceived susceptibility and benefits and negatively associated with perceived barriers. These findings provide preliminary evidence of the instrument’s validity and reliability, although independent cross-validation is warranted.